Immediate demolding concrete block and method for manufacturing the same
By using glass cullet and blast furnace slag powder in a carbonation-cured concrete composition, the manufacturing of concrete blocks addresses the challenge of solar panel waste reuse and carbon emissions, improving strength and durability.
Patent Information
- Application Number
- JP2024095106
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-20
- Filing Date
- 2024-06-12
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2044-06-12
AI Technical Summary
The increasing amount of solar panel glass waste and the need to reduce carbon dioxide emissions in concrete block manufacturing processes necessitate the efficient reuse of glass waste materials while minimizing environmental impact.
Manufacturing immediate detached concrete blocks using a concrete composition with glass cullet as an aggregate and incorporating blast furnace slag powder as a binding material, which is cured through carbonation to reduce alkaline components and promote carbon dioxide fixation.
This approach increases the reuse of glass waste materials, reduces carbon dioxide emissions, and enhances the strength and durability of concrete blocks by suppressing alkaline silica reactions and promoting carbonation within the blocks.
Smart Images

Figure 2025015436000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a quick-removable concrete block and a method for producing the same. [Background technology]
[0002] Patent Document 1 discloses a method for producing a quick-removable concrete block by using concrete containing glass cullet obtained from waste glass as aggregate. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2001-26009 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, the introduction of solar power generation facilities as a renewable energy source has been progressing. On the other hand, the amount of discarded glass from solar panels is also increasing year by year, making its reuse an issue. For this reason, in manufacturing concrete blocks, it is necessary not only to simply reuse the waste glass as described in Patent Document 1, but also to increase the amount of recycled glass. Furthermore, from the perspective of the SDGs (Sustainable Development Goals), in addition to reusing the waste glass, it is also required to reduce carbon dioxide emissions in the manufacturing process of concrete blocks.
[0005] An object of the present invention is to provide a concrete block that can increase the amount of recycled glass waste and reduce carbon dioxide emissions. [Means for solving the problem]
[0006] The present invention relates to an instant-removable concrete block produced by pressurizing and vibrating a concrete composition for an instant-removable method, which contains glass cullet as an aggregate, molding the composition, and then curing the composition by carbonation. The concrete composition contains, by mass, more than 30% and not more than 90% of ground granulated blast furnace slag as a binder in the concrete composition.
[0007] The present invention also provides a method for producing a quick-removable concrete block, which includes a forming step of pressurizing and vibrating a concrete composition for quick-removal systems, which contains glass cullet as aggregate, to form a block body, and a curing step of carbonating and curing the block body, in which the concrete composition contains, by mass, more than 30% and not more than 90% ground granulated blast furnace slag as a binder in the concrete composition. Effect of the Invention
[0008] According to the present invention, it is possible to reduce the amount of carbon dioxide emissions during the manufacturing process of concrete blocks and to increase the amount of recycled glass waste. [Brief description of the drawings]
[0009] [Figure 1] 1 is a flowchart showing a manufacturing process of a quick-removable concrete block according to an embodiment of the present invention. [Diagram 2] 1 is a graph showing comparative results of bending strength tests. [Diagram 3] 1 is a graph showing plots of bending strength test results. [Figure 4] 1 is a graph showing comparative results of bending strength tests. [Diagram 5] This is an image showing the fracture surface of a concrete block taken during a test to measure neutralization depth. [Figure 6] 1 is a graph showing comparative results of an accelerated expansion rate test. [Figure 7] 1 is a graph showing comparative results of bending strength tests. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, a quick-removable concrete block and a manufacturing method thereof according to an embodiment of the present invention will be described.
[0011] The instant-removable concrete block according to the embodiment of the present invention is a solidified molded body produced by pressurizing and vibrating a concrete composition containing glass cullet as an aggregate to mold it, and then subjecting it to carbonation curing, and is used, for example, as an interlocking block used for paving roads and sidewalks, or a revetment block used to prevent erosion in rivers and coastlines. However, the uses of the concrete block are not limited to these.
[0012] The concrete composition for the immediate demolding method used to manufacture the immediate demolding concrete block according to the embodiment of the present invention contains water (W) and glass cullet (RGC: recycled glass cullet) as an aggregate, and also contains ground granulated blast furnace slag (BFS) in a mass ratio of more than 30% and not more than 90% of the binder (cement material) in the concrete composition. The concrete composition for the immediate demolding method also contains an air-entraining agent for immediate demolding as an admixture (AD).
[0013] Glass cullet (RGC) is made by finely crushing discarded glass bottles and the like into cullet or powder, and in recent years, there has been an increase in RGC produced by crushing the glass from solar panels that have been discarded due to deterioration over time in solar power generation facilities that have been introduced in large quantities as renewable energy. The use of glass cullet as aggregate is desirable from the perspective of environmental consideration, as it leads to a reduction in the use of natural resources such as gravel that have traditionally been used as aggregate.
[0014] On the other hand, because glass cullet has a lower density than the general aggregates that have been used up until now, increasing the ratio (substitution rate) of glass cullet to the total aggregate weight of a quick-removable concrete block reduces strength such as bending strength. For example, the Glass Recycling Council's "Guidelines for Recycled Glass Aggregate for the Manufacturing of Quick-Removable Concrete Products" stipulates that the substitution rate (mass ratio) of glass cullet should be 8% or less of the aggregate volume.
[0015] In addition, glass cullet, which is a silica-based material, reacts with alkaline components produced by the hydration reaction of binders such as ordinary Portland cement to form alkaline silica gel (ASR), which may cause cracks to occur in the future.
[0016] For this reason, in this embodiment, carbonation curing is performed to reduce the alkaline components generated by the hydration reaction through carbonation, and by adding ground granulated blast furnace slag, which has a lower alkaline component content than ordinary Portland cement, to the concrete composition, the alkaline components themselves are reduced, thereby suppressing the occurrence of alkali-silica reaction.
[0017] Aggregates include glass cullet, as well as natural aggregates such as gravel, artificial aggregates such as crushed stone, and recycled aggregates as fine aggregates (S) and coarse aggregates (G) defined in JIS A 1102:2014, etc. As described later, the entire amount of the aggregate may be glass cullet, the entire amount of the coarse aggregate (G) of the aggregate may be glass cullet, or the entire amount of the fine aggregate (S) of the aggregate may be glass cullet.
[0018] Ground granulated blast furnace slag (BFS) is a fine powder specified in JIS A 6206:2013 "Ground granulated blast furnace slag for concrete" and its types are classified according to specific surface area (cm 2 / g), any of the ground granulated blast furnace slag may be used in this embodiment.
[0019] Compared to Portland cement, the amount of carbon dioxide emissions generated during the manufacturing process of granulated blast furnace slag, or the so-called CO2 emission unit (CO2 emission coefficient), is approximately one-thirtieth that of Portland cement. Therefore, by increasing the proportion of granulated blast furnace slag contained in the binder in the concrete composition, it is possible to reduce the amount of carbon dioxide emissions involved in the production of instant-removable concrete blocks.
[0020] The main binder of the concrete composition for the immediate demolding method is Portland cement such as ordinary Portland cement (OPC), and ground granulated blast furnace slag is mixed into the binder as an admixture. The binder of the concrete composition for the immediate demolding method may be an efficient blast furnace cement (ECM), which is a mixed cement in which ground granulated blast furnace slag (BFS) and a cement material such as ordinary Portland cement (OPC) are mixed in advance. The Portland cement is not limited to ordinary Portland cement (OPC), and other types of Portland cement, such as high-early-strength Portland cement and moderate-heat Portland cement, may be used.
[0021] There are three types of blast furnace cement (ECM), in which the mass ratio of ground granulated blast furnace slag to the total binder is Type A, which is more than 5% and not more than 30%, Type B, which is more than 30% and not more than 60%, and Type C, which is more than 60% and not more than 70%, but in this embodiment, Type B or Type C, preferably Type C, is used from the viewpoint of reducing the alkaline components as described above and from the viewpoint of reducing the carbon dioxide emissions involved in the production of concrete blocks. Note that, as described later, the mass ratio of ground granulated blast furnace slag may be increased to about 90%.
[0022] In addition, concrete compositions for the instant demolding method may contain, as admixtures, calcium silicate gamma phase (γ:γCS) capable of chemically bonding with carbon dioxide gas or recycled calcium carbonate (Et) solidified with carbon dioxide gas. By including an admixture capable of chemically bonding with carbon dioxide gas or an admixture solidified with carbon dioxide gas in the concrete composition, it is possible to further reduce the amount of carbon dioxide emissions involved in the production of instant demolding concrete blocks.
[0023] As admixtures capable of chemically bonding with carbon dioxide, instead of calcium silicate gamma phase, blast furnace slag, steelmaking slag, copper slag, fly ash, sewage sludge incineration ash, biomass combustion ash, silica fume, rice husk ash, hydrated lime, quicklime, natural pozzolana, and the like may be used. As admixtures made by solidifying carbon dioxide, instead of recycled calcium carbonate, recycled calcium bicarbonate, recycled magnesium carbonate, recycled magnesium bicarbonate, regenerated sodium carbonate, regenerated sodium bicarbonate, regenerated potassium carbonate, regenerated sodium bicarbonate, shells, and the like may be used.
[0024] Next, a manufacturing process for the quick-removable concrete block will be described with reference to FIG.
[0025] First, in step S11, the weights of raw materials contained in the concrete composition, such as aggregate containing glass cullet, binder such as cement, and water, are measured (measurement step). The mixing ratio of the raw materials will be described later.
[0026] The weighed raw materials are then fed into a mixer in the next step S12 and mixed for about 3 to 5 minutes (mixing step). The concrete composition thus produced is an ultra-solid concrete with a slump value of less than 2.5 mm, so-called zero slump concrete, and is a concrete composition for immediate demolding.
[0027] The concrete composition produced in step S12 is poured into a formwork attached to a vibration molding machine in the following step S13.
[0028] The vibration molding machine is a table vibrator or a press vibrator, and in step S13, the concrete composition for the immediate demolding method filled in the formwork is vibrated using this vibration molding machine at a predetermined vibration frequency (e.g., 6000 rpm) for a predetermined time (e.g., 5 seconds) to mold it into a predetermined shape (molding process).
[0029] When molding is completed, the block molded body is removed from the mold form, and in the next step S14, the removed block molded body is cured in the following three patterns for comparison.
[0030] In the first pattern, the product is cured indoors for 14 days in air without being cured by carbonation, in the second pattern, the product is cured indoors for 2 days in air and then for another 7 days in a carbonation curing device (carbonation curing process), and in the third pattern, the product is cured indoors for 7 days in air and then for another 7 days in a carbonation curing device (carbonation curing process). Carbonation curing is performed, for example, under conditions of a temperature of 50°C, humidity of 50%, and carbon dioxide concentration of 80%. Note that the carbonation curing conditions are not limited to these.
[0031] After curing under the prescribed conditions, the block compact becomes a solidified compact having a prescribed strength.
[0032] Through the above-mentioned steps, a quick-removable concrete block is produced from a concrete composition for quick-removable concrete blocks containing glass cullet as an aggregate.
[0033] Next, the results of bending strength tests performed on concrete blocks having the compositions shown in Tables 1 and 2 below will be described with reference to Table 3, Figs. 2 and 3.
[0034] In the following tables, W means water, B means binder, W / B means water-binder ratio, s / a means fine aggregate ratio, OPC means ordinary Portland cement, BB means blast-furnace cement type B equivalent, ECM means blast-furnace cement type C, BFS means ground granulated blast-furnace slag, S means fine aggregate, G means coarse aggregate, RGC means glass cullet, AD means admixture (AE agent for immediate demolding), and their respective densities (g / cm 3 ) are as follows:
[0035] OPC:3.16, ECM:2.96, BFS:2.91, S:2.63, G:2.63, RGC:2.44, AD:1.03
[0036] [Table 1]
[0037] [Table 2]
[0038] Comparative Example 1 is a mix in which only ordinary Portland cement is used as a binder, and 7% (mass ratio) of the total aggregate amount (fine aggregate + coarse aggregate) is replaced with glass cullet. Comparative Example 2 is a mix in which blast furnace cement type C is used as a binder instead of ordinary Portland cement, and the aggregate is not replaced with glass cullet (RGC replacement rate: 0%). Examples 1 to 5 are mixes in which blast furnace cement type C is used as a binder instead of ordinary Portland cement, and the aggregate is replaced with glass cullet (RGC replacement rate: 7 to 100%). Example 11 is a mix in which the binder in Example 2 is a binder equivalent to blast furnace cement type C (a binder containing 68% ordinary Portland cement and blast furnace slag ground powder by mass) instead of blast furnace cement type C. Note that glass cullet is used as a part of the coarse aggregate in Examples 1 to 3, and the entire amount of coarse aggregate is replaced with glass cullet in Example 4. In Example 5, the entire amount of aggregate, that is, the entire amount of fine aggregate and coarse aggregate, is replaced with glass cullet.
[0039] The results of the bending strength test performed on the test pieces of the quick-removable concrete blocks manufactured with the mix proportions of each of the Examples and Comparative Examples shown in Tables 1 and 2 are shown in Table 3, Figures 2 and 3. The size of the test pieces was 10 cm x 20 cm x 5 cm, and the bending strength test was performed in accordance with the "Bending Strength Test of Products" of JIS A 5363:2016. Note that Figure 2 is a graph comparing the bending strength of Comparative Example 1 and Example 1, and Figure 3 is a graph plotting the bending strength of Comparative Example 2 and Examples 1 to 4 cured in the second pattern, and Example 5 cured in the third pattern.
[0040] [Table 3]
[0041] As shown in Fig. 2, when Comparative Example 1 and Example 1, which have the same glass cullet replacement rate, are compared, in the first curing pattern (air curing for 14 days), Comparative Example 1, in which only ordinary Portland cement, which has excellent strength development, is used as the binder, has a higher bending strength, whereas in the second curing pattern (air curing for 2 days, carbonation curing for 7 days), Example 1, in which blast-furnace cement type C, which has a relatively small amount of alkaline components, is used as the binder, has a higher bending strength. When carbonation curing was performed, in Comparative Example 1, the alkali concentration at the start of curing was high, which slowed down the progress of carbonation, whereas in Example 1, the alkali concentration at the start of curing was relatively low, which allowed carbonation to progress quickly to the center of the concrete block, and it is presumed that a large amount of calcium carbonate, a stable mineral, was generated inside and densified.
[0042] Even in cases where the inclusion of glass cullet in the aggregate may reduce bending strength, the bending strength can be improved by combining the inclusion of ground granulated blast furnace slag in the binder with carbonation curing in the curing process, compared to when the binder is made only of ordinary Portland cement.
[0043] Here, when the instant-removable concrete block manufactured through the above-mentioned process is used as an interlocking block, for example, as specified in JIS A 5371:2016, the interlocking strength is 5N / mm 2 , 3N / mm for sidewalks 2 It is required that the bending strength is 100% or more.
[0044] As shown in Table 3 and Figure 3, when the replacement rate of glass cullet was increased from 7% (Example 1) to 100% (Example 5), the amount of natural coarse aggregate, which has high aggregate strength, decreased, and the bending strength decreased with the increase in the replacement rate. However, in all mixes, the bending strength was within the standard value (5N / mm 2 ) and the result was higher.
[0045] Even when the entire amount of aggregate was replaced with glass cullet (Example 5), the standard value (5 N / mm 2 ), the replacement rate (mass ratio) of glass cullet can be made greater than 8% as stipulated in the above-mentioned "Guidelines for recycled glass aggregate for the production of quickly removable concrete products," and can be increased, for example, to 100%.
[0046] Up to a replacement rate of 31%, glass cullet with a particle size of 2 to 5 mm is used in place of coarse aggregate such as No. 7 crushed stone, and for parts exceeding 31% replacement rate, fine glass cullet with a particle size of less than 1.2 mm is used in place of fine aggregate such as crushed sand.
[0047] In the graph of FIG. 3, the change in the tendency at a replacement rate of about 30% is believed to be due to the fact that the particle size of the glass cullet being replaced becomes smaller at a replacement rate of about 30%, and it can be said that the effect of fine glass cullet on bending strength is smaller than that of glass cullet with a particle size of 2 to 5 mm.
[0048] Furthermore, as shown in Table 3, the bending strength of Example 2 and Example 11 are almost the same, which indicates that there is no significant difference in strength performance between the case where blast-furnace cement type C is used as the binder and the case where a binder equivalent to blast-furnace cement type C, which is produced by mixing ordinary Portland cement and blast-furnace slag powder instead of blast-furnace cement type C, is used.
[0049] Next, the effect of the blending amount of ground granulated blast furnace slag on bending strength will be described with reference to the graph in Fig. 4, which compares the results of bending strength tests conducted on test pieces of quick-removable concrete blocks manufactured with the blending amounts of each of the Examples and Comparative Examples shown in Tables 4 and 5. The size of the test pieces was 10 cm x 20 cm x 5 cm, and the bending strength tests were conducted in accordance with JIS A 5363:2016 "Bending strength test of products."
[0050] [Table 4]
[0051] [Table 5]
[0052] Comparative Example 3 is a mix in which the binder is only ordinary Portland cement, and 20% (by mass) of the total aggregate (fine aggregate + coarse aggregate) is replaced with glass cullet. Examples 12 to 15 are mixes in which the glass cullet replacement rate is 20% like Comparative Example 3. Example 12 is a mix in which the binder is equivalent to blast furnace cement type B by previously mixing 40% by mass of ground granulated blast furnace slag with ordinary Portland cement. Example 13 is a mix in which the binder is type C blast furnace cement, and the ground granulated blast furnace slag is contained at 68% by mass. Example 14 is a mix in which the ground granulated blast furnace slag is mixed into the binder as an admixture, and the ground granulated blast furnace slag is contained at 80% by mass. Example 15 is a mix in which the ground granulated blast furnace slag is mixed into the binder as an admixture, and the ground granulated blast furnace slag is contained at 90% by mass.
[0053] As shown in FIG. 4, when the amount of ground granulated blast furnace slag contained in the binder was increased from 40% (Example 12) to 90% (Example 15), the bending strength decreased with an increase in the mass ratio of ground granulated blast furnace slag. However, in all the blends, the bending strength was within the standard value (5N / mm 2 The bending strength of Comparative Example 3 was measured after curing in the first pattern, and the bending strength of Examples 12 to 15 was measured after curing in the third pattern.
[0054] In this way, even when the mass ratio of ground granulated blast furnace slag was set to a ratio higher than that of blast furnace cement type C or equivalent (Examples 14 and 15), the standard value (5 N / mm 2 ), the mass ratio of ground granulated blast furnace slag can be increased, for example, to 90%. However, in order to ensure sufficient bending strength and improve durability, the mass ratio of ground granulated blast furnace slag is preferably set to about 80%.
[0055] Furthermore, according to the results shown in Figure 4, when the binder is equivalent to blast-furnace cement type B (Example 12), it is possible to improve the bending strength compared to when the binder is only ordinary Portland cement, just as in the case when the binder is blast-furnace cement type C.
[0056] Next, the effect of carbonation curing in reducing the alkaline components in a concrete block will be explained with reference to Figures 5 and Table 6, which show the results of carbonation depth measurement tests conducted on concrete blocks having the compositions shown in Tables 4 and 5 above.
[0057] Figure 5 is a photograph of a concrete block fracture surface sprayed with a phenolphthalein solution (1%) in the method for measuring the neutralization depth of concrete specified in JIS A 1152:2018, and the area that turns reddish purple indicates that it is alkaline. A color photograph of the photograph shown in Figure 5 should be submitted as reference material in the project submission form.
[0058] [Table 6]
[0059] As shown in Figure 5 (Reference Material) and Table 6, the higher the mass proportion of ground granulated blast furnace slag, the deeper the carbonation depth after carbonation curing. This shows that by including ground granulated blast furnace slag in the concrete composition, carbonation during carbonation curing progresses quickly to the inside of the concrete block, and carbon dioxide is efficiently solidified within the concrete block.
[0060] Furthermore, as shown in Figure 5 (reference material), the area of the area in which the phenolphthalein solution turned reddish purple was reduced by carbonation curing, which means that the amount of alkaline components in the concrete block was reduced. As a result, it is possible to suppress the alkali-silica reaction (ASR), in which glass cullet, which is siliceous, reacts with alkaline components to form alkaline silica gel.
[0061] Next, the influence of the glass cullet replacement rate on the expansion rate will be described with reference to Fig. 6, which shows the results of an accelerated expansion rate test conducted to confirm the inhibitory effect of the above-mentioned alkali-silica reaction. The accelerated expansion rate test was conducted after curing a concrete block having the composition shown in Table 7 in the third pattern.
[0062] [Table 7]
[0063] The expansion rate shown in Figure 6 was measured by the saturated NaCl solution immersion method (Danish method), which is one of the accelerated expansion rate tests, and is measured by immersing a test piece cut to a specified size in a saturated NaCl solution maintained at a specified temperature (50°C) for a specified curing period (13 weeks). The criteria for the expansion rate in this method are "no expansion" if it is less than 0.1%, "expansion" if it is 0.4% or more, and "unclear" if it is 0.1-0.4%.
[0064] As shown in FIG. 6, in Comparative Example 2, which does not contain glass cullet, the expansion rate is nearly 0%, whereas the expansion rate increases as the glass cullet replacement rate increases. However, even in Example 5, in which the glass cullet replacement rate is 100%, the expansion rate is judged to be "non-expandable."
[0065] Even in the case where the glass cullet replacement rate was relatively high in this way (Example 5), the accelerated expansion test determined the concrete to be "non-expansive." This shows that the risk of deterioration due to alkali-silica reaction (ASR) was sufficiently kept low by the effect of reducing the alkaline components through the above-mentioned carbonation curing and the effect of including in the concrete composition ground granulated blast-furnace slag, which has a lower alkaline component content than ordinary Portland cement.
[0066] Next, the results of bending strength tests performed on concrete blocks having the compositions shown in Tables 8 and 9 below and the effect of reducing carbon dioxide emissions will be described with reference to Table 10.
[0067] In Tables 8 and 9, γ stands for carbonated admixture (γCS), and Et stands for recycled calcium carbonate (admixture). Their respective densities (g / cm 3 ) are as follows, and other descriptions are the same as in Tables 1 and 2.
[0068] γ: 3.06, Et: 2.46
[0069] [Table 8]
[0070] [Table 9]
[0071] Example 21 is a mix in which the binder is blast-furnace cement type C as in Examples 1 to 5, and 20% (mass ratio) of the total aggregate amount (fine aggregate + coarse aggregate) is replaced with glass cullet. Example 22 is a mix in which 30% of the blast-furnace cement type C of Example 21 is replaced with a carbonation admixture (γC2S), which is an admixture that chemically bonds with carbon dioxide. Example 23 is a mix in which 30% of the blast-furnace cement type C of Example 21 is replaced with recycled calcium carbonate, which is an admixture in which carbon dioxide has been fixed in advance. Comparative Example 1 has the same mix as Comparative Example 1 in Tables 1 and 2, and glass cullet is used as the coarse aggregate in both mixes.
[0072] Table 10 shows the results of bending strength tests performed on test pieces of the quick-removable concrete blocks manufactured using the mix proportions of each of the Examples and Comparative Examples shown in Tables 8 and 9, as well as the calculation results of the reduction in carbon dioxide emissions. The size of the test pieces was 10 cm x 20 cm x 5 cm, and the bending strength tests were performed in accordance with JIS A 5363:2016 "Bending strength test of products."
[0073] The CO2 emission unit (CO2 emission coefficient) used in the calculation of carbon dioxide emissions was the value shown in the 2012 Japan Society of Civil Engineers Concrete Library 134 (e.g., Portland cement: 766.6 (kg-CO2 / t), crushed sand: 3.7 (kg-CO2 / t), crushed stone: 2.9 (kg-CO2 / t), ground granulated blast furnace slag: 26.5 (kg-CO2 / t)). Since glass cullet is waste, the CO2 emission unit was set to 0, and since the amount of admixture is small, the carbon dioxide emissions were set to 0. The CO2 emission unit of the carbonated admixture (γ) was set to the value (125 (kg-CO2 / t)) shown in the following reference 1, and the CO2 emission unit of the recycled calcium carbonate (Et) was set to the value (-390 (kg-CO2 / t)) shown in the following reference 2.
[0074] References 1) Torichika et al.: "CO2SUICOM: Environmentally Friendly Concrete with Zero CO2 Emissions," Cement Concrete, Vol. 786, pp. 26-31, 2012 Reference 2) Toshiyuki Yagi et al.: Environmentally friendly light calcium carbonate made from Ecotancal CO2, Civil Engineering, Vol. 62, No. 11, pp. 87-90, November 2021
[0075] The amount of CO2 reduction in Table 10 is the amount of CO2 emission (C1-C2) of each mix from the amount of CO2 emission (C1 in Comparative Example 1) emitted in the process of manufacturing the standard concrete block manufactured using the ordinary Portland cement of Comparative Example 1, and the amount of actual CO2 emission is the amount of CO2 emission (C1) emitted in the process of manufacturing the concrete block of each mix minus the amount of CO2 fixed in the concrete block by carbonation curing (C2) from the amount of CO2 emission (C1) emitted in the process of manufacturing the concrete block of each mix. The amount of CO2 fixation (C2) is measured by analyzing the total carbon content (TC) of the test pieces of Examples 21 to 24. Specifically, after carbonation curing, samples taken from the fracture surface of the concrete block are subjected to a hydration stop treatment with acetone, crushed, and measured with a total organic carbon meter.
[0076] [Table 10]
[0077] As shown in Table 10, the bending strength of Example 22, which contains an admixture that chemically bonds with carbon dioxide, and the bending strength of Example 23, which contains an admixture that fixes carbon dioxide, are equivalent to the bending strength of Example 21, which does not contain these admixtures. In both mixes, the bending strength is within the above-mentioned standard value (5 N / mm 2 ) and the result was higher.
[0078] Furthermore, as shown in Table 10, the CO2 reduction rate (the ratio of CO2 reduction to the CO2 emissions of the benchmark Comparative Example 1) of Example 22, which contains an admixture that chemically bonds with carbon dioxide, was 96.6%, while the CO2 reduction rate of Example 23, which contains an admixture that fixes carbon dioxide, was 105.5%, making it carbon negative. Even in Example 21, which does not contain these admixtures, the CO2 reduction rate was 86.3%.
[0079] In this way, by using a mix that contains an admixture that chemically bonds with carbon dioxide or an admixture that fixes carbon dioxide, it is possible to significantly reduce carbon dioxide emissions without reducing bending strength, and even by simply using blast-furnace cement type C as the binder, it is possible to significantly reduce carbon dioxide emissions compared to when ordinary Portland cement is used as the binder. Furthermore, even if the binder is blast-furnace cement type B or equivalent, it is estimated that it will be possible to reduce carbon dioxide emissions compared to when ordinary Portland cement is used as the binder, even if the effect is not as great as when blast-furnace cement type C is used as the binder.
[0080] Next, the effect on bending strength of the admixtures that chemically bond with carbon dioxide and admixtures that fix carbon dioxide will be described with reference to Fig. 7, which shows the results of bending strength tests carried out on test pieces of quick-removable concrete blocks manufactured with the mix proportions of the Examples and Comparative Examples shown in Table 11 below. The size of the test pieces was 10cm x 20cm x 5cm, and the bending strength tests were carried out in accordance with JIS A 5363:2016 "Bending strength test of products".
[0081] [Table 11]
[0082] As described above, Comparative Example 2 is a mix in which the binder is Type C blast-furnace cement and the aggregate is not replaced with glass cullet, Comparative Example 4 is a mix in which 30% of the Type C blast-furnace cement of Comparative Example 2 is replaced with a carbonated admixture (γC2S) and 30% of the Type C blast-furnace cement is replaced with recycled calcium carbonate, and Example 24 is a mix in which 20% (by mass) of the total aggregate amount (fine aggregate + coarse aggregate) of Comparative Example 4 is replaced with glass cullet.
[0083] As shown in FIG. 7, the bending strength is reduced by the inclusion of an admixture that chemically bonds with carbon dioxide and an admixture that fixes carbon dioxide in the binder, and is further reduced by replacing a portion of the aggregate with glass cullet. However, the bending strength of Example 24 is within the standard value (5 N / mm 2 The bending strength shown in Figure 7 was measured after curing with the third pattern.
[0084] In this way, even when the binder contained an admixture that chemically bonds with carbon dioxide and an admixture that immobilizes carbon dioxide, and when part of the aggregate was replaced with glass cullet (Example 24), the standard value (5 N / mm 2), it is possible to significantly reduce carbon dioxide emissions while increasing the amount of glass waste used. Note that in Example 24, the admixture that chemically bonds with carbon dioxide gas and the admixture that fixes carbon dioxide gas are mixed together, but as in Examples 22 and 23, for example, these may be mixed separately.
[0085] According to the above embodiment, the following effects are achieved.
[0086] The above-mentioned quick-removable concrete block is produced by pressurizing and vibrating a concrete composition for quick-removable concrete containing glass cullet as aggregate to form it, and then carbonating it to cure it. The concrete composition contains, by mass, more than 30% and not more than 90% of ground granulated blast furnace slag as a binder in the concrete composition.
[0087] The more glass cullet is contained in the aggregate, the higher the possibility of the alkali-silica reaction occurring, which will cause future cracks; however, by combining the reduction in the alkaline components themselves by adding ground granulated blast furnace slag to the concrete composition and the reduction in the alkaline components produced by the hydration reaction by carbonation curing in the curing process, it is possible to suppress the occurrence of the alkali-silica reaction compared to when the binder is only Portland cement.
[0088] This makes it possible to increase the amount of glass cullet contained in the aggregate, which results in an increase in the amount of glass waste used for solar panels, etc., while reducing the amount of natural resources such as gravel used as aggregate. In addition, the occurrence of cracks caused by alkali-silica reactions will be suppressed in the future, so the bending strength will be able to reach the standard value (5N / mm 2 ), the replacement rate of glass cullet can be made to exceed 8% as specified in the "Guidelines for recycled glass aggregate for the manufacture of quick-removable concrete products."
[0089] In addition, by combining the inclusion of ground granulated blast furnace slag, which has a smaller CO2 emission unit value than Portland cement, in the concrete composition with carbonation curing, which solidifies carbon dioxide within the concrete block, it is possible to significantly reduce the amount of carbon dioxide emitted during the manufacturing process of concrete blocks, compared to when the binder is only Portland cement.
[0090] Furthermore, there is a risk that the strength of the concrete block will decrease as the amount of glass cullet contained in the aggregate increases; however, by combining the inclusion of blast furnace slag powder in the concrete composition with carbonation curing in the curing process, carbonation can be advanced to the center of the concrete block, producing a large amount of calcium carbonate inside the concrete block, thereby improving the strength and durability of the concrete block compared to when the binder is only Portland cement.
[0091] Thus, according to the embodiment, by combining the inclusion of granulated blast furnace slag in the concrete composition with carbonation curing in the curing step, it is possible to simultaneously achieve the effects of increasing the amount of glass cullet contained in the aggregate, reducing the amount of carbon dioxide emitted in the concrete block manufacturing process, and improving the strength and durability of the concrete block, compared to when the binder is only Portland cement.
[0092] In addition, the following modified examples are also within the scope of the present invention, and it is possible to combine the configuration shown in the modified example with the configuration described in the above embodiment, or to combine the configurations described in the different modified examples below.
[0093] In the above embodiment, the glass cullet is mainly used as the coarse aggregate. Alternatively, the powdered glass cullet may be mainly used as the fine aggregate. Also, the glass cullet may be used as a part of the coarse aggregate and a part of the fine aggregate.
[0094] In the above embodiment, the binder is mainly C-type blast-furnace cement, but the binder may be equivalent to C-type blast-furnace cement (a binder containing more than 60% and not more than 70% by mass of ordinary Portland cement and ground granulated blast-furnace slag). The binder may be B-type blast-furnace cement or equivalent to B-type blast-furnace cement (a binder containing more than 30% and not more than 60% by mass of ordinary Portland cement and ground granulated blast-furnace slag).
[0095] Although the embodiments of the present invention have been described above, the above-mentioned embodiments merely show some of the application examples of the present invention, and it is not intended that the technical scope of the present invention be limited to the specific configurations of the above-mentioned embodiments.
Claims
1. A quick-release concrete block produced by pressurizing and vibrating a quick-release concrete composition containing glass cullet as an aggregate, forming the composition, and then curing the composition by carbonation, The concrete composition contains ground granulated blast furnace slag in an amount of more than 30% and not more than 90% by mass of the binder in the concrete composition. Instant demoldable concrete blocks.
2. The glass cullet is more than 8% by mass of the aggregate in the concrete composition; 2. The quick-removable concrete block according to claim 1.
3. At least a part or all of the coarse aggregate of the aggregate is the glass cullet.
2. The quick-removable concrete block according to claim 1.
4. At least a part or all of the fine aggregate of the aggregate is the glass cullet.
2. The quick-removable concrete block according to claim 1.
5. The concrete composition includes an admixture capable of chemically bonding with carbon dioxide gas or an admixture that has solidified carbon dioxide gas.
2. The quick-removable concrete block according to claim 1.
6. A method for producing a quick-release concrete block, comprising: A forming step of forming a block body by pressurizing and vibrating a concrete composition for a quick demolding method containing glass cullet as an aggregate; A curing step of carbonating the block body, The concrete composition contains ground granulated blast furnace slag in an amount of more than 30% and not more than 90% by mass of the binder in the concrete composition. A method for manufacturing quick-release concrete blocks.
Citation Information
Patent Citations
Cement mixture containing glass chips
JP2006104020A
Quick disconnect block for pavement
JP2010236309A
Method for manufacturing carbon dioxide gas fixation concrete
JP2023096668A
Production of instantly demoldable concrete block
JP2001026009A
Cited By
Cement admixture, cement composition, and cement hardened body
WO2025173733A1